The Monitoring, Learning and Evaluation Community of Practice embraces smartphones to support monitoring activities - International Potato Center (2016)
We used smartphones to collect registration data from 326 sweetpotato vine multipliers and yield data from 99 households in nine Sub-Saharan Africa countries.